Association between sedentary behavior and chronic kidney disease in Korean adults - Ye Seul Jang; Yu Shin Park; Hyunkyu Kim; Kyungduk Hurh; Eun-Cheol Park; Suk-Yong Jang (BMC Public Health, 2023)
Abstract Background Chronic kidney disease (CKD) is a significant health care burden, with a worldwide prevalence of approximately 11%. The general population spends over 50% of the awake time sedentary activities. However, to the best of our knowledge, no study has evaluated the association between sedentary time and CKD, with a focus on both kidney damage and kidney function, in the South Korean population. Accordingly, the present study aimed to address this gap in the knowledge. Method We used data from the 8th Korea National Health and Nutrition Examination Survey. The analysis included 9,534 participants, especially excluded those who had been diagnosed with kidney disease or who were currently undergoing treatment. Sedentary behavior was self-reported by the participants. An estimated glomerular filtration rate (eGFR) and/or albuminuria were used as measures for detection of CKD according to the guidelines of the Kidney Disease Improving Global Outcomes. We analyzed the data using multiple logistic regression. Results Among the women, the risk of CKD was significantly greater among those who sat for ≥ 12 h/d relative to those who sat for < 6 h/d, after adjusting for physical activity and other covariates (odds ratio [OR]: 1.45, 95% confidence interval [CI]: 1.01–2.06). Similarly, among those who sat over 12 h/d, those who engaged in low levels of physical activity had a higher risk of CKD than those who engaged in high levels of activity (OR: 1.65, 95% CI: 1.04–2.61). No statistically significant results were found for men. Conclusion Excessive sedentary behavior was associated with an increased risk of CKD, especially albuminuria, regardless of the level of physical activity, only in women. These findings emphasize the importance of avoiding excessive sitting for a long time and increasing overall physical activity levels.